Musculoskeletal fatigue in cancer patients with cachexia: A systematic review - Tegar Fitriyana Sukaya Karso; Syamsunarno, Mas Rizky Anggun; Defi, Irma Ruslina (European Journal of Oncology and Environmental Health, 2026)
Background: Cachexia is a multifactorial syndrome commonly seen in cancer patients, marked by significant weight and muscle loss, and is strongly associated with cancer-related fatigue (CRF). This condition results from an imbalance in muscle protein homeostasis, exacerbated by systemic inflammation and metabolic dysregulation. Understanding the relationship between muscle wasting and fatigue in cachexia can provide insights into potential therapeutic interventions. Methods: A systematic review was conducted using databases such as PubMed, ScienceDirect, and EMBASE. Keywords included “cachexia,” “cancer,” “biomarker,” and “fatigue.” Inclusion criteria were studies involving cancer patients with cachexia, with fatigue as a primary outcome and musculoskeletal system biomarkers as key variables. After screening 3,434 articles, two studies met the inclusion criteria. Results: Both studies emphasized the critical role of muscle mass and strength in fatigue. The first study demonstrated significant negative correlations between handgrip strength (HGS), quadriceps strength (QS), skeletal muscle mass index (SMMI), and fatigue levels (measured by the Brief Fatigue Inventory, BFI) in male patients, suggesting muscle wasting as a primary contributor to fatigue. The second study (n=83) found no significant associations between fatigue and inflammatory cytokines such as IL-1b, IL-6, IL-8, and TNF-α, challenging the conventional view of inflammation as the primary driver of fatigue in cachexia. Discussion: The findings highlight muscle bioenergetic inefficiency and metabolic disturbances as key mechanisms underlying fatigue in cancer cachexia, with inflammatory pathways playing a less significant role. Gender differences in musculoskeletal markers’ influence on fatigue underscore the need for tailored interventions. Conclusion: Muscle wasting is a central determinant of fatigue in cancer cachexia, while the role of inflammation remains inconclusive. Further research is essential to explore alternative mechanisms and develop targeted therapies.